ACCESS TO JUSTICE FOR THE POOR AT THE RELIGIOUS COURT OF BOGOR IN 2021 - Regina Selviana, Wella; Anggie Mustika, Desty (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
One of the basic rights of citizens is the right to obtain fair legal certainty (access to justice) which applies to all citizens. The number of poor people who need Legal Aid Institutions (LBH) in the litigation process, therefore the government tries to overcome it by providing services in the form of providing funds that can be accessed through advocates. To achieve access to justice for the community, Law Number 16 of 2011 concerning Legal Aid was issued. The government also provides financial assistance for the poor through the Religious Courts by waiving court fees (prodeo), in Article 237 of HIR Law no. 48/20 jo no. 50/2009 explicitly states that the state bears the costs of the case for justice seekers who cannot afford it, so the state is obliged to fulfill the mandate of the law. Therefore, this study will discuss about Access to Justice for the Poor regarding the Exemption of Case Fees (Prodeo) at the Bogor Religious Court.